A Preference for Preferred Shares - De Leon, Augusto L. (Philippine Management Review, 2016)
Preferred stocks have not been a popular source of external financing in the Philippine capital markets.  Yet it offers advantages like assured control for common stockholders, flexibility in dividend service, perpetual term and strengthened equity based on the issuing company. The main reason for the lack of availment of this financing source by companies is its high cost to the issuer.  This paper proposes that this impediment be eliminated by making preferred stock dividends tax deductible.  This move would encourage the issuance of preferred stocks, help stimulate the Philippine capital market and channel financing to support corporate investments.